Anthropometric growth pattern in Ethiopian infants and children : an evaluation based on different international growth references - De Stefano, Gian Franco (Array, 2009)
Abstract: At the population level international growth references have been widely used as useful tools to assess a number of situations, i.e.: to predict local and general emergencies related to food and nutrition; to assess the equity of distribution of economic resources within and between communities; to evaluate the suitability of weaning practices and to screen and following at-risk groups. Nevertheless, recently several concerns were raised regarding the adequacy of currently existing growth references involving study design, population sample, time validity, and evaluation of infant and children well-being in terms of food availability and nutritional adequacy. As in the past, discussion involve also suitability of local or national reverences versus the international ones. This paper focusses on the re-evaluation of the main auxometric indexes, i.e.: height for age, weight for height and BMI in a sample of infant and children aged between 24 and 120 months from urban and rural Ethiopia. Previous evaluation based on the NCHS-1977 growth references led to striking results in terms of growth retardation while a recent evaluation based on NCHS-2000 (NHANES) growth references gave better but contradictory pictures. As consequence, concerns on the adequacy of international references use in infant and children growth assessment in the developing countries seem to be widely justified while local or national well built growth references should offer the possibility for a most realistic evaluation